Colostomy: building autonomy for self-care (Research, Society and Development, 2020)
Objective: to research, according to the literature, the knowledge of patients with colostomy in relation to self-care. Method: integrative research, using the electronic databases Latin American Literature in Health Sciences (LILACS) and Scientific Electronic Library Online (SCIELO), with a six-year time frame. Results: 18 scientific articles were selected, which showed that the condition of being ostomized has an impact on the way the individual sees his body and changes personal values ​​and family roles, in addition to causing stigmatization by third parties. Conclusion: The adaptation of the colostomy patient goes through an acceptance process, in which the physiological modification means more than a simple procedure, in this sense, self-care has a positive influence on quality of life. Several factors influence the patient's self-care, as well as adherence and motivation for treatment and proposed interventions. Knowing them is fundamental for understanding the challenges of the stoma care process.